2017
DOI: 10.1039/c7tc02369c
|View full text |Cite
|
Sign up to set email alerts
|

Novel iridium(iii) complexes bearing dimesitylboron groups with nearly 100% phosphorescent quantum yields for highly efficient organic light-emitting diodes

Abstract: The solution-processed OLEDs based on IrIII complexes with high ΦP can show a maximum ηL of 85.1 cd A−1, ηP of 69.7 lm W−1, and ηext of 28.1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…The EQE of the PMD‐Ir‐3‐based device is among the highest values for the iridium‐based red PhOLEDs (see Figure ). [4a–d,6,7,24] Additionally, the EQEs remained as high as 24.6% and 17.9% at high luminance values of 1000 and 10 000 cd m −2 , respectively. The low EQE roll‐off was comparable to the reported red PhOLEDs.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The EQE of the PMD‐Ir‐3‐based device is among the highest values for the iridium‐based red PhOLEDs (see Figure ). [4a–d,6,7,24] Additionally, the EQEs remained as high as 24.6% and 17.9% at high luminance values of 1000 and 10 000 cd m −2 , respectively. The low EQE roll‐off was comparable to the reported red PhOLEDs.…”
Section: Resultsmentioning
confidence: 96%
“…The low EQE roll‐off was comparable to the reported red PhOLEDs. [24f,25] For example, Han et al reported a series of (MDQ) 2 Ir(acac)‐based devices with EQE roll‐off values above 27% at a normal operation luminance of 1000 cd m −2 …”
Section: Resultsmentioning
confidence: 99%
“…The phosphorescent emitters incorporating heavy metals can reach an IQE of nearly 100% by enhancing electron spin-orbit coupling (Baldo et al, 1998;Adachi et al, 2001;Xia et al, 2014). However, the applications of phosphorescent materials containing heavy metals are limited owing to their high cost and environmental contamination (Li et al, 2013;Liu et al, 2017a;Wang et al, 2018). Accordingly, it is critically important to develop novel metal-free materials, which can be functionalized as efficient emitters and exhibit environment friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…As we known, phosphors are generally heavy metal complexes. The spin–orbit coupling (SOC) of heavy metal (Ir, Pt, et al) ion cores will significantly enhance the energy transfer processes between singlet and triplet states [intersystem crossing process (ISC) from S 1 to T 1 and phosphorescent decay from T 1 to S 0 ], allowing heavy metal complexes to achieve phosphorescence efficiently (Baldo et al, 1998; Liu X. et al, 2015; Liu B. et al, 2017). Correspondingly, in new type exciplexes, the decay routes of excited exciplexes will be also affected by the heavy metal phosphor cores.…”
Section: Introductionmentioning
confidence: 99%